THE IMPACT OF EDUCATION USING THE REALISTIC TEACHING MODEL ON LEARNING ARTISTIC PERFORMANCE IN HAMMER THROWING FOR STUDENTS - Haider Taha Abdul Redha Mazloom; Muhannad Muhammed Kazem (Galaxy International Interdisciplinary Research Journal, 2023)
The importance of this study lies in the researchers' attempt to contribute new insights to the scientific literature by introducing and utilizing the Realistic Teaching Model in educating students in the artistic performance of hammer throwing. The goal is to prepare competent learners who possess a wealth of ideas, experience, and knowledge to leverage in the future. Additionally, the study explores the proper way to learn the art of hammer throwing, as many traditional teaching methods do not give students a significant role in the learning process. In contrast, modern strategies, including the Realistic Teaching Model, have been effective in engaging learners and facilitating the acquisition of information.